Hush! A Thai Lullaby - Ho, Minfong (New York : Orchard books, 1996)
A lullaby which asks animals such as a lizard, monkey, and water-buffalo to be quiet and not disturb the sleeping baby.
Keywords: Thai Lullaby; Baby; Animals; Picture book